UPAYA GURU DALAM MENINGKATKAN KREATIVITAS MELALUI METODE PEMBERIAN TUGAS PADA ANAK USIA DINI DI TAMAN KANAK-KANAK ANUGRAH KECAMATAN PALAKKA KABUPATEN BONE - Iting, Andi (Institut Agama Islam Negeri Bone, 2019)
This research discusses about the efforts of teachers to improve children’s creativity in Anugrah kindergarten at Palakka District of Bone. The purposes of this study were understanding the descriptions of the children’s creativity and applying the task giving method in improving a children’s creativity and knowing the efforts was made by teachers to improve the creativity of children in Anugrah kindergarten at Palakka District of Bone. in obtaining the data in this study, researcher used a qualitative research method, with descriptive analysis. The used data collection techniques in this research is observation, interview, and documentation. Based on the results of the research conducted in Anugrah kindergarten at Palakka District of Bone, it could be concluded that the creativity of children was initially still not optimal due to family factors which have not yet understood the importance of the children's creativity development. Therefore, teachers find a suitable method to develop children’s creativity, and teachers found a suitable method, which is task giving method, in which it provides chance and discretion to a child in completing their duties in accordance to the creativity of each children. By administering this task giving method, eventually proved that children's creativity was developed, by several children who won drawing and colouring competitions.Keywords: Children’s creativity; task giving method